Certificate Programs: Certified Internal Auditor. - Stettler, Howard F. (The Accounting Review, 1975)
Abstract This article presents information on the Certified Internal Auditor (CIA) certificate program offered by the Institute of Internal Auditors Inc. The program of the Institute leading to the designation CIA is the newest of the three certificate programs that exist within the field of accountancy in the United States. The senior program, by a wide margin, is the Certified Public Accountant (CPA), which dates back to the initial enabling legislation in New York in 1896. The current number of CPAs holding certificates issued by 50 states and the District of Columbia is estimated by the AICPA as being more than 150,000. The CIA Program is intended primarily to achieve recognition of demonstrated competence in internal auditing. The Board of Directors of the Institute, an international association serving some 11,000 members throughout the world, under the direction of a nine-member Board of Regents appoints the Program. In contrast to the CPA certificate, which is essentially a license to practice and only secondarily a form of recognition of achievement, neither the CMA nor the CIA certificate has any licensing or other aspects of restricting the right to practice a particular form of accounting activity.